The Influence of Human Resource Quality and Infrastructure Support on Digital Village Public Service Innovation (DIGIDES) in Ambon City - Fatmala, Andi Nurpratiwi; Sakir, Ahmad Rosandi; Mayasari, Ayu Dewi (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This study aims to analyze the influence of human resource quality and infrastructure support on digital public service innovation in villages across Ambon City. The background of this research lies in the growing need for public services that are faster, more transparent, and accountable through the adoption of digital technology at the village level. A quantitative approach with multiple linear regression analysis was employed, using data collected from surveys of village officials and service users. The findings reveal that human resource quality has a positive and significant effect on digital public service innovation. This highlights the crucial role of competence, skills, and digital literacy among village officials in managing technology-based service systems. Furthermore, infrastructure support also shows a significant influence, particularly in terms of internet accessibility, technological equipment, and adequate supporting facilities. The simultaneous test (F-test) indicates that human resource quality and infrastructure support jointly contribute to the enhancement of digital public service innovation. In conclusion, strengthening the capacity of village officials and providing sufficient infrastructure development are essential strategies for driving the transformation of public services toward a more effective, efficient, and community-oriented digital governance system at the village level.